Angular dependences of ellipsometric parameters of thin Cr and Ti films under surface polariton excitation - Shybiko, Ya.A.; Shaykevich, I.A.; Melnichenko, L.Yu. (Functional Materials, 2006)
The 80 Å and 100 Å thick Cr films and 45 Å thick Ti ones were obtained bу the vacuum evaporation on glass substrates. The ellipsometric parameter ψ (azimuth of the restored linear polarization ψ) was measured at λ = 546.1 nm both at the air side and the glass one under various angles of incidence. In the second case, the surface polaritons were excited using the Kretchman method bу means of a transparent semi-cуlinder. Parameters measured at the air side were used to calculate optical constants n and k. Ellipsometric parameters under surface polariton excitation were calculated. The obtained theoretical results conform to the experimental data. The last fact testifies that the Airу formulas can be used to calculate both ellipsometric parameters and reflection and transmission coefficients under surface polariton excitation. Плiвка Ti товщиною 45 Å i плiвки Cr товщиною 80 Å i 100 Å одержувалися методом вакуумного напилення на склянi пiдкладки i для них вимiрювалися кутовi залежностi елiпсометричних параметрiв, а саме азимуту вiдновленої лiнiйної поляризацiї як з боку повiтря, так i з боку скла, тобто при збудженнi поверхневих поляритонiв за методом Кречмана за допомогою прозорого напiвцилiндра при довжинi хвилi λ = 546,1 нм. За даними, одержаними з боку повiтря, обчислювалися оптичнi сталi плiвок n i k, розраховувалися елiпсометричнi параметри при збудженнi поверхневих поляритонiв. Одержанi теоретичнi результати узгоджуються з експериментальними даними. Останнє свiдчить про те, що формули Ейрi можуть бути застосованi до розрахункiв як елiпсометричних параметрiв, так i коефiцiєнтiв вiдбивання i пропускання при збудженнi поверхневих поляритонiв. Угловые зависимости эллипсометрических параметров, а именно азимута восстановленной линейной поляризации ψ, измерялись для тонкой пленки Т i толщиной 45 Å и Cr толщиной 80 Å и 100 Å (пленки были получены методом вакуумного напыления на стеклянные подложки) как со стороны воздуха, так и со стороны стекла (то есть, при возбуждении поверхностных поляритонов по методу Кречмана при помощи прозрачного полуцилиндра на длине волны λ = 546,1 нм). По данным, полученным со стороны воздуха, вычислялись оптические постоянные пленок n и k и рассчитывались эллипсометрические параметры при возбуждении поверхностных поляритонов. Полученные теоретические результаты согласовываются с экспериментальными данными. Последнее свидетельствует о том, что формулы Эйри можнo использовать для расчетов как эллипсометрических параметров, так и коэффициентов отражения и пропускания при возбуждении поверхностных поляритонов.